2019
DOI: 10.3310/hta23630
|View full text |Cite
|
Sign up to set email alerts
|

Different strategies for pharmacological thromboprophylaxis for lower-limb immobilisation after injury: systematic review and economic evaluation

Abstract: Background Thromboprophylaxis can reduce the risk of venous thromboembolism (VTE) during lower-limb immobilisation, but it is unclear whether or not this translates into meaningful health benefit, justifies the risk of bleeding or is cost-effective. Risk assessment models (RAMs) could select higher-risk individuals for thromboprophylaxis. Objectives To determine the clinical effectiveness and cost-effectiveness of different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 224 publications
0
33
0
Order By: Relevance
“…Several risk assessment models (RAM) have already been derived for use in this patient population, aiming to tailor thromboprophylaxis strategies at presumed high risk and limit financial costs, opportunity costs, and side effects . The current evidence base for RAMs is very limited, and estimates of sensitivity and specificity are subject to substantial uncertainty . Improving the evidence base for RAMs is a key research priority and external validation studies are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several risk assessment models (RAM) have already been derived for use in this patient population, aiming to tailor thromboprophylaxis strategies at presumed high risk and limit financial costs, opportunity costs, and side effects . The current evidence base for RAMs is very limited, and estimates of sensitivity and specificity are subject to substantial uncertainty . Improving the evidence base for RAMs is a key research priority and external validation studies are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review was undertaken in accordance with the general principles recommended in the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement . This review was part of a larger project on thromboprophylaxis for lower limb immobilization that was registered on the PROSPERO international prospective register of systematic reviews (CRD42017058688) . The full protocol is available here (https://www.journalslibrary.nihr.ac.uk/programmes/hta/1518706/#/).…”
Section: Methodsmentioning
confidence: 99%
“…We found that both LMWH and fondaparinux significantly reduced the odds of clinically detected DVT, PE and any VTE. Intervention appeared to halve the risk of VTE across all classifications 23…”
Section: Introductionmentioning
confidence: 95%
“…Can pharmacological thromboprophylaxis reduce this morbidity burden and, if so, by what margin? We performed a recently updated systematic review and network meta-analysis to compare any pharmacological intervention against control for this defined population 22 23. This review included the Prevention of Thrombosis after Lower Leg Plaster Cast (POT-CAST) trial,21 which has reignited debate on this important topic, and other recent randomised studies assessing the novel use of fondaparinux for this indication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation